(* Title: HOL/Algebra/Module.thy
Author: Clemens Ballarin, started 15 April 2003
Copyright: Clemens Ballarin
*)
theory Module
imports Ring
begin
section \<open>Modules over an Abelian Group\<close>
subsection \<open>Definitions\<close>
record ('a, 'b) module = "'b ring" +
smult :: "['a, 'b] => 'b" (infixl "\<odot>\<index>" 70)
locale module = R?: cring + M?: abelian_group M for M (structure) +
assumes smult_closed [simp, intro]:
"[| a \<in> carrier R; x \<in> carrier M |] ==> a \<odot>\<^bsub>M\<^esub> x \<in> carrier M"
and smult_l_distr:
"[| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
(a \<oplus> b) \<odot>\<^bsub>M\<^esub> x = a \<odot>\<^bsub>M\<^esub> x \<oplus>\<^bsub>M\<^esub> b \<odot>\<^bsub>M\<^esub> x"
and smult_r_distr:
"[| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
a \<odot>\<^bsub>M\<^esub> (x \<oplus>\<^bsub>M\<^esub> y) = a \<odot>\<^bsub>M\<^esub> x \<oplus>\<^bsub>M\<^esub> a \<odot>\<^bsub>M\<^esub> y"
and smult_assoc1:
"[| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
(a \<otimes> b) \<odot>\<^bsub>M\<^esub> x = a \<odot>\<^bsub>M\<^esub> (b \<odot>\<^bsub>M\<^esub> x)"
and smult_one [simp]:
"x \<in> carrier M ==> \<one> \<odot>\<^bsub>M\<^esub> x = x"
locale algebra = module + cring M +
assumes smult_assoc2:
"[| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
(a \<odot>\<^bsub>M\<^esub> x) \<otimes>\<^bsub>M\<^esub> y = a \<odot>\<^bsub>M\<^esub> (x \<otimes>\<^bsub>M\<^esub> y)"
lemma moduleI:
fixes R (structure) and M (structure)
assumes cring: "cring R"
and abelian_group: "abelian_group M"
and smult_closed:
"!!a x. [| a \<in> carrier R; x \<in> carrier M |] ==> a \<odot>\<^bsub>M\<^esub> x \<in> carrier M"
and smult_l_distr:
"!!a b x. [| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
(a \<oplus> b) \<odot>\<^bsub>M\<^esub> x = (a \<odot>\<^bsub>M\<^esub> x) \<oplus>\<^bsub>M\<^esub> (b \<odot>\<^bsub>M\<^esub> x)"
and smult_r_distr:
"!!a x y. [| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
a \<odot>\<^bsub>M\<^esub> (x \<oplus>\<^bsub>M\<^esub> y) = (a \<odot>\<^bsub>M\<^esub> x) \<oplus>\<^bsub>M\<^esub> (a \<odot>\<^bsub>M\<^esub> y)"
and smult_assoc1:
"!!a b x. [| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
(a \<otimes> b) \<odot>\<^bsub>M\<^esub> x = a \<odot>\<^bsub>M\<^esub> (b \<odot>\<^bsub>M\<^esub> x)"
and smult_one:
"!!x. x \<in> carrier M ==> \<one> \<odot>\<^bsub>M\<^esub> x = x"
shows "module R M"
by (auto intro: module.intro cring.axioms abelian_group.axioms
module_axioms.intro assms)
lemma algebraI:
fixes R (structure) and M (structure)
assumes R_cring: "cring R"
and M_cring: "cring M"
and smult_closed:
"!!a x. [| a \<in> carrier R; x \<in> carrier M |] ==> a \<odot>\<^bsub>M\<^esub> x \<in> carrier M"
and smult_l_distr:
"!!a b x. [| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
(a \<oplus> b) \<odot>\<^bsub>M\<^esub> x = (a \<odot>\<^bsub>M\<^esub> x) \<oplus>\<^bsub>M\<^esub> (b \<odot>\<^bsub>M\<^esub> x)"
and smult_r_distr:
"!!a x y. [| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
a \<odot>\<^bsub>M\<^esub> (x \<oplus>\<^bsub>M\<^esub> y) = (a \<odot>\<^bsub>M\<^esub> x) \<oplus>\<^bsub>M\<^esub> (a \<odot>\<^bsub>M\<^esub> y)"
and smult_assoc1:
"!!a b x. [| a \<in> carrier R; b \<in> carrier R; x \<in> carrier M |] ==>
(a \<otimes> b) \<odot>\<^bsub>M\<^esub> x = a \<odot>\<^bsub>M\<^esub> (b \<odot>\<^bsub>M\<^esub> x)"
and smult_one:
"!!x. x \<in> carrier M ==> (one R) \<odot>\<^bsub>M\<^esub> x = x"
and smult_assoc2:
"!!a x y. [| a \<in> carrier R; x \<in> carrier M; y \<in> carrier M |] ==>
(a \<odot>\<^bsub>M\<^esub> x) \<otimes>\<^bsub>M\<^esub> y = a \<odot>\<^bsub>M\<^esub> (x \<otimes>\<^bsub>M\<^esub> y)"
shows "algebra R M"
apply intro_locales
apply (rule cring.axioms ring.axioms abelian_group.axioms comm_monoid.axioms assms)+
apply (rule module_axioms.intro)
apply (simp add: smult_closed)
apply (simp add: smult_l_distr)
apply (simp add: smult_r_distr)
apply (simp add: smult_assoc1)
apply (simp add: smult_one)
apply (rule cring.axioms ring.axioms abelian_group.axioms comm_monoid.axioms assms)+
apply (rule algebra_axioms.intro)
apply (simp add: smult_assoc2)
done
lemma (in algebra) R_cring:
"cring R"
..
lemma (in algebra) M_cring:
"cring M"
..
lemma (in algebra) module:
"module R M"
by (auto intro: moduleI R_cring is_abelian_group
smult_l_distr smult_r_distr smult_assoc1)
subsection \<open>Basic Properties of Algebras\<close>
lemma (in algebra) smult_l_null [simp]:
"x \<in> carrier M ==> \<zero> \<odot>\<^bsub>M\<^esub> x = \<zero>\<^bsub>M\<^esub>"
proof -
assume M: "x \<in> carrier M"
note facts = M smult_closed [OF R.zero_closed]
from facts have "\<zero> \<odot>\<^bsub>M\<^esub> x = (\<zero> \<odot>\<^bsub>M\<^esub> x \<oplus>\<^bsub>M\<^esub> \<zero> \<odot>\<^bsub>M\<^esub> x) \<oplus>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub> (\<zero> \<odot>\<^bsub>M\<^esub> x)" by algebra
also from M have "... = (\<zero> \<oplus> \<zero>) \<odot>\<^bsub>M\<^esub> x \<oplus>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub> (\<zero> \<odot>\<^bsub>M\<^esub> x)"
by (simp add: smult_l_distr del: R.l_zero R.r_zero)
also from facts have "... = \<zero>\<^bsub>M\<^esub>" apply algebra apply algebra done
finally show ?thesis .
qed
lemma (in algebra) smult_r_null [simp]:
"a \<in> carrier R ==> a \<odot>\<^bsub>M\<^esub> \<zero>\<^bsub>M\<^esub> = \<zero>\<^bsub>M\<^esub>"
proof -
assume R: "a \<in> carrier R"
note facts = R smult_closed
from facts have "a \<odot>\<^bsub>M\<^esub> \<zero>\<^bsub>M\<^esub> = (a \<odot>\<^bsub>M\<^esub> \<zero>\<^bsub>M\<^esub> \<oplus>\<^bsub>M\<^esub> a \<odot>\<^bsub>M\<^esub> \<zero>\<^bsub>M\<^esub>) \<oplus>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub> (a \<odot>\<^bsub>M\<^esub> \<zero>\<^bsub>M\<^esub>)"
by algebra
also from R have "... = a \<odot>\<^bsub>M\<^esub> (\<zero>\<^bsub>M\<^esub> \<oplus>\<^bsub>M\<^esub> \<zero>\<^bsub>M\<^esub>) \<oplus>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub> (a \<odot>\<^bsub>M\<^esub> \<zero>\<^bsub>M\<^esub>)"
by (simp add: smult_r_distr del: M.l_zero M.r_zero)
also from facts have "... = \<zero>\<^bsub>M\<^esub>" by algebra
finally show ?thesis .
qed
lemma (in algebra) smult_l_minus:
"[| a \<in> carrier R; x \<in> carrier M |] ==> (\<ominus>a) \<odot>\<^bsub>M\<^esub> x = \<ominus>\<^bsub>M\<^esub> (a \<odot>\<^bsub>M\<^esub> x)"
proof -
assume RM: "a \<in> carrier R" "x \<in> carrier M"
from RM have a_smult: "a \<odot>\<^bsub>M\<^esub> x \<in> carrier M" by simp
from RM have ma_smult: "\<ominus>a \<odot>\<^bsub>M\<^esub> x \<in> carrier M" by simp
note facts = RM a_smult ma_smult
from facts have "(\<ominus>a) \<odot>\<^bsub>M\<^esub> x = (\<ominus>a \<odot>\<^bsub>M\<^esub> x \<oplus>\<^bsub>M\<^esub> a \<odot>\<^bsub>M\<^esub> x) \<oplus>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub>(a \<odot>\<^bsub>M\<^esub> x)"
by algebra
also from RM have "... = (\<ominus>a \<oplus> a) \<odot>\<^bsub>M\<^esub> x \<oplus>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub>(a \<odot>\<^bsub>M\<^esub> x)"
by (simp add: smult_l_distr)
also from facts smult_l_null have "... = \<ominus>\<^bsub>M\<^esub>(a \<odot>\<^bsub>M\<^esub> x)"
apply algebra apply algebra done
finally show ?thesis .
qed
lemma (in algebra) smult_r_minus:
"[| a \<in> carrier R; x \<in> carrier M |] ==> a \<odot>\<^bsub>M\<^esub> (\<ominus>\<^bsub>M\<^esub>x) = \<ominus>\<^bsub>M\<^esub> (a \<odot>\<^bsub>M\<^esub> x)"
proof -
assume RM: "a \<in> carrier R" "x \<in> carrier M"
note facts = RM smult_closed
from facts have "a \<odot>\<^bsub>M\<^esub> (\<ominus>\<^bsub>M\<^esub>x) = (a \<odot>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub>x \<oplus>\<^bsub>M\<^esub> a \<odot>\<^bsub>M\<^esub> x) \<oplus>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub>(a \<odot>\<^bsub>M\<^esub> x)"
by algebra
also from RM have "... = a \<odot>\<^bsub>M\<^esub> (\<ominus>\<^bsub>M\<^esub>x \<oplus>\<^bsub>M\<^esub> x) \<oplus>\<^bsub>M\<^esub> \<ominus>\<^bsub>M\<^esub>(a \<odot>\<^bsub>M\<^esub> x)"
by (simp add: smult_r_distr)
also from facts smult_r_null have "... = \<ominus>\<^bsub>M\<^esub>(a \<odot>\<^bsub>M\<^esub> x)" by algebra
finally show ?thesis .
qed
end